Evaluation of Copeptin during Pulmonary Exacerbation in Cystic Fibrosis - Wojsyk-Banaszak, I.; Sobkowiak, P.; Jończyk-Potoczna, K.; Narożna, B.; Langwiński, W.; Szczepanik, M.; Kycler, Z.; Bręborowicz, A.; Szczepankiewicz, A. (Mediators of Inflammation, 2019)
Copeptin was found to be a stable biomarker of inflammation and stress response in cardiac, renal, metabolic, and respiratory conditions such as pneumonia. The aim of this study was to investigate the copeptin levels in biological fluids (serum and sputum supernatant) of cystic fibrosis pediatric patients during pulmonary exacerbation and remission and to investigate the possible influence of copeptin levels on disease severity and quality of life. Copeptin serum concentrations were measured in 28 pediatric cystic fibrosis (CF) patients: 13 in stable condition and 15 during pulmonary exacerbation. In 10 CF patients, copeptin was also measured in the sputum. In all the patients, we assessed complete blood count, BMI, sputum culture, lung function, and chest imaging (with Brasfield score). The severity of symptoms was assessed using the Shwachman-Kulczycki (SK) score, and the quality of life was assessed with the Cystic Fibrosis Quality of Life Questionnaire-Revised (CFQ-R). Copeptin concentrations in serum and sputum supernatant was measured using an ELISA kit. Statistical analysis was done in Statistica v.12. Serum and sputum copeptin levels were higher in CF patients during pulmonary exacerbation than in a stable period, but the differences were not significant (p=0.58 and p=0.13, respectively). Copeptin did not correlate significantly with any clinical, laboratory, or spirometry markers of exacerbation. There was, however, a significant inverse correlation between the serum copeptin level and symptoms severity (r=‐0.77, p=0.008) and radiological changes (r=‐0.5626, p=0.036) during pulmonary exacerbation in pediatric CF patients. Copeptin also inversely correlated with the quality of life domains in CF patients: vitality and eating habits, mostly loss of appetite (p=0.031 and p=0.016, respectively). Copeptin may be useful to identify patients with a higher risk of deterioration to improve their outcomes.